Topologies between compact and uniform convergence on function spaces - S. Kundu; R. A. McCoy (International Journal of Mathematics and Mathematical Sciences)
This paper studies two topologies on the set of all continuous real-valued functions on a Tychonoff space which lie between the topologies of compact convergence and uniform convergence.